Formation mechanism of the Lidang circular structure in the Guangxi Province. Issue 4 (30th July 2019) - Yan, Pan; Xiao, ZhiYong; Ma, YiZhen; Wang, YiChen; Pu, Jiang
Abstract : The Lidang circular structure in the center of the Guangxi Province is about 8 km in diameter. This structure appears as an abnormal shallow depression that has disturbed the rather harmonic regional joint systems. Its unique occurrence in the whole region, the circular morphology, negative topography, and the spatial distribution of interior and exterior strata are all consistent with those of impact craters that are formed by asteroidal or cometary collision. To test the impact hypothesis, we carried out both field investigation and remote sensing study of this structure. Regional geological history suggests that if the impact hypothesis were correct, the impact event should have occurred at or after the Early Permian. Field investigation found that the strata inside and outside the crater are dominated by parallel stacks of Lower and Upper Permian limestone that have various thicknesses and different mud contents. The layers of limestone within and outside the circular structure have identical attitudes; no structural disturbances were visible in the outcrops. Field investigations provide conclusive evidence against the impact cratering hypothesis. A high‐resolution digital elevation model shows that the spatial distribution of rounded mountains within the structure is controlled by faint but continual extension of joints, suggesting that the crater interior has gone through a much higher degree of erosion. Therefore, regional joints that had once existed within the crater are preserved less well than exterior terrains, forming the abruptly disrupted circular depression. Differential erosion, as the possible formation mechanism of the Lidang structure, is consistent with the different mud contents found between the interior and exterior limestone. The circular outline of this structure may correspond to the shape of the original deposition basin. In conclusion, the Lidang circular structure is a polje formed by karstification, not an astrobleme.